Pengaruh Kontrol Diri Terhadap Tingkat Religiusitas Siswa Kelas VIII di SMP Negeri 4 Pare Kediri - Julianne Kamelia Riza (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
Self-control is an activity of individual self-control of their behavior where an individual has faith in their God which is called religiosity. The difference in the level of religiosity triggers various problems in society, especially students who are at puberty, and develop in a variety of environments. This research was conducted on grade VIII students at SMP Negeri 4 Pare Kediri, aims to determine the students' self-control and religiosity level, as well as how the influence of self-control on the level of religiosity. This type of research is quantitative research with self-control as the independent variable, and the level of religiosity as the dependent variable. The instrument used in this study was the self-control scale and the level of religiosity given to 72 subjects who were taken by random sampling. Hypothesis testing in this study using linear regression test with SPSS for Windows 16.0. The test results of the SPSS for Windows 16.0 program stated that these students on average had good self-control and a high level of religiosity. Based on the R-square value, there is an influence between the variable X and Y in the weak category of 20%, while 80% is influenced by other factors that are not studied.